Development of multimedia edition "Pets" - Комарова, Дина Владимировна; Бизюк, Андрей Валерьевич (Eastern-European Journal of Enterprise Technologies, 2012)
In the article the results of studies on the development of interactive multimedia training applications "Pets" are presented. The study was carried out similar analysis of the publications identified common elements necessary for the electronic publications of this type, with recommendations for further developments